Ballasts for tubular fluorescent lamps. Specification for ballasts for use with lamps used in the UK not included in BS 1853 'Tubular fluorescent lamps for general lighting service' Part 1 'Specification for internationally specified lamps' Part 2, (1st September 1986) - British Standards Institution,
No abstract available